The use of salivary biomarkers to monitor metabolic changes caused by physical exercise - A literature review (Research, Society and Development, 2024)
Introduction: Saliva is crucial for oral health, reflecting overall health due to its complex composition. With easy collection and a rich source of clinical information, saliva is promising for investigating physiological responses to exercise. Objective: To analyze the potential and limitations of salivary markers in monitoring biochemical changes induced by physical exercise. Methods: This literature review used databases like SciELO, PubMed, and Google Scholar with the keywords: "biomarkers," "saliva," "monitoring," and "physical exercise." A total of 272 studies were found. Inclusion criteria were: addressing the guiding question; original research and/or systematic reviews from the last 14 years; published in English, Portuguese, or Spanish; and having significant results. Ten studies were selected. Results: Salivary biomarkers were effective in assessing immune and endocrine status, monitoring oxidative stress and muscle damage, identifying sports concussions, and evaluating recovery methods' efficiency. Quantitative differences were observed between genders. The collection technique is simple, safe, inexpensive, and non-invasive but requires rigorous methodology and individual athlete analysis. Conclusion: Saliva is a rich source of biomarkers reflecting physiological responses to exercise, despite limitations like individual variability and the need for personalized monitoring.